Some aspects of the taxonomy and biology of adult spirurine nematodes parasitic in fishes: a review - Moravec, Frantisek (Folia parasitologica, 2007)
About 300 species belonging to four superfamilies (Gnathostomatoidea, Habronematoidea, Physalopteroidea and Thelazioidea) of the nematode suborder Spirurina are known as the adult parasites of freshwater, brackish-water and marine fishes. They are placed in four families, of which the Gnathostomatidae, including Echinocephalus with a few species and the monotypic Metaleptus, are parasites of elasmobranchs, whereas Ancyracanthus contains one species in teleosts; the Physalopteridae is represented in fish by four genera, Bulbocephalus, Heliconema, Paraleptus and Proleptus, each with several species in both elasmobranchs and teleosts. The majority of fish spirurines belongs to the Rhabdochonidae, which includes 10 genera (Beaninema, Fellicola, Hepatinema, Heptochona, Johnstonmawsonia, Megachona, Pancreatonema, Prosungulonema, Rhabdochona and Vasorhabdochona) of species parasitizing mainly teleosts, rarely elasmobranchs, and the Cystidicolidae with about 23 genera (Ascarophis, Caballeronema, Capillospirura, Comephoronema, Crenatobronema, Cristitectus, Ctenascarophis, Cyclozone, Cystidicola, Cystidicoloides, Johnstonmawsonoides, Metabronema, Moravecnema, Neoascarophis, Parascarophis, Prospinitectus, Pseudascarophis, Pseudoproleptus, Salvelinema, Similascarophis, Spinitectoides, Spinitectus, Sterliadochona), with many species parasitic in teleosts only. Because of difficulties in studying fish spirurines, associated with their morphological and biological peculiarities, most species of these parasites are poorly known. It is apparent that their present classification system does not reflect phylogenetic relationships and a taxonomic revision of this nematode group, based on detailed morphological (including SEM and TEM), life history and molecular studies of individual species, is quite necessary. In Cystidicolidae, several genera have been based on details in the cephalic structures visible only with the aid of SEM, but it will be evident whether or not these tiny features are of generic importance only when more cystidicolids are described using SEM and comparative molecular data become available. Data on the biology of fish spirurines are scarce. In known cases, their life cycles involve aquatic arthropods (crustaceans or insects) as intermediate hosts, in which, sometimes, the larvae undergo a precocious development and may even attain adulthood and become gravid in these invertebrates; sometimes, fish paratenic hosts are known to occur in cystidicolids parasitizing as adults piscivorous definitive hosts. Some spirurine species are pathogenic and are known as causative agents of serious fish diseases. Consequently, further detailed studies on fish spirurines are significant not only from the theoretical viewpoint, but they may also have practical implications.
Keywords: ryby; Life Cycle Stages; stadia vývoje; Fishes; Head; ústa; Ovum; ovum; Mouth; Animals; hlava; zvířata; Spirurida